ILMU KALIGRAFI DALAM TINJAUAN SEJARAH PERADABAN ISLAM - Rodhiatul Syakila; Putri Nabila Alifia Sirait (Yayasan Haiah Nusratul Islam, 2025)
The history of calligraphy is an important record of past events that helps us understand events that have occurred before. Calligraphy is recognized as an art form that has existed since the time of the Prophet Muhammad until the reign of Ali bin Abi Talib. This research uses qualitative methods with a descriptive design to explore the history and development of calligraphy from the time of Rasulullah SAW to the Abbasid period. The aim of using this instrument is to investigate in depth various unique aspects of the cases studied, so that researchers can understand the phenomenon and its context as a whole. The history of Islamic calligraphy shows significant evolution from the time of Rasulullah SAW to the Abbasid period. Initially, Arabic calligraphy during the time of the Prophet was characterized by simple writing forms and less emphasis on aesthetic aspects.